MENINGKATKAN HASIL BELAJAR DAN BERPIKIR KRITIS MENGGUNAKAN PROBLEM SOLVING - Esterlina Rumi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
This study aims to find out the problem-solving learning process so that it can improve students' science learning outcomes and critical thinking skills of students of grade VII SMP Negeri 4 Sewon Lesson Year 2016/2017. The research was conducted in SMP Negeri 4 Sewon with research object of class VII B SMP Negeri 4 Sewon. From the result of the research, it is found that there is an increase from cycles I to cycle II with 36,4% presentation to 97,0% while the result of student critical thinking skill presentation at cycle I 27,3% and at cycle II 51,5%. Based on the average of learning outcomes and questionnaires, there is an effect of using Problem Solving learning model from Cycle I to Cycle II.